Photosynthetic Production Determines Bottom Water Oxygen Variations in the Upwelling Coastal South China Sea Over Recent Decades - Zhu, Xiaowei; Jia, Guodong; Tian, Yuhang; Mo, Aibin; Xu, Weihai; Miao, Li; Xu, Shendong; Yan, Wen (Frontiers in Earth Science, 2021)
Dissolved oxygen (DO) in seawater is fundamental to marine ecosystem health. How DO in coastal upwelling areas responds to upwelling intensity under climate change is of particular interest and vital importance, because these productive regions account for a large fraction of global fishery production and marine biodiversity. The Yuedong Upwelling (YDU) in the coastal northern South China Sea can be served as a study case to explore long-term responses of DO to upwelling and climate due to minor influence of riverine input. Here, bottom water DO conditions were recovered by sedimentary C2822/5,22 ratios of steroids in three short cores, with lower ratio value indicating higher DO concentration. The ratio records showed oscillations in varying degrees and exhibited no clear trends before ~1980s, after which, however, there occurred a persistent decreasing trend or basically remained at lower values. Thus inferred DO variations by the C2822/5,22 ratio records are not compatible with regional YDU-involved physical processes under climate change, such as southwesterly wind-induced onshore advection of reduced-oxygenated source waters from outer shelf and oceanic warming that would rather lead to less oxygenation in bottom waters in recent decades. Intriguingly, the alcohol records of n-C20:1/C285,22 and br-C15/C285,22 ratios, indicative of the relative strengths between biogeochemical oxygen consumption (i.e., by zooplankton and microbes) and photosynthetic oxygen production (i.e., by phytoplankton), changed almost in parallel with the C2822/5,22 records in three cores. Accordingly, we propose that net photosynthetic oxygen production outweighs source water- and warming-induced increasing deoxygenation in the study area. This study may suggest an important biogeochemical mechanism in determining bottom water DO dynamics in shallow coastal upwelling regions with minor contribution of riverine input.